Network effects, conformism and misbehavior in Brazilian classrooms - Santos, Luan Falcão Daniel (2016)
For understanding how networks a ect the behavior of individuals, speci - cally the behavior os students in the last year of high school inside the classroom, we estimate a model of Network e ects, the Local-average model for two behavioral variables: doing an exam without being prepared and cheating in an exam, in order to understand how the behavior of individual's friends a ects his or her behavior. It was found a positive and statistically signi cant e ect for the network e ect of the probability of doing an exam without being prepared, and a positive, but not signi cant e ect for the network e ect of the probability of cheating in an exam. This result shows that policies or actions aiming the reduction of the probability of a student do an exam without being prepared have what is called social multiplier e ect, because besides this policy change the behavior of the student regarding this variable, his or her change of behavior a ects positively the behavior of people in his or her network.